Evaluation of entries in Gradshteyn and Ryzhik employing the method of brackets - Ivan Gonzalez; Karen T. Kohl; V. H. Moll (Scientia Series A: Mathematical Sciences, 2025)
The method of brackets was created for the evaluation of definite integrals appearing in the resolution of Feynman diagrams. This method consists of a small number of heuristic rules and it is quite easy to apply. The first of these is Ramanujan’s Master Theorem, one of his favorite tools to evaluate integrals. The current work illustrates its applicability by evaluating a variety of entries from the classical table of integrals by I. S. Gradshteyn and I. M. Ryzhik.
Keywords: Definite integrals; method of brackets; tables of integrals.